Erratum to “Frequency-Domain Large-Signal Modeling and Stability Analysis for Dispatchable Virtual Oscillator Controlled Grid- Connected Converters” - Zheran Zeng; Yin Sun; Dongsheng Yang (IEEE Open Journal of Power Electronics)
This addresses errors in [1]. All subscripts using $\upalpha$ and $\upbeta$ should have been non-italic, to match their formatting in the figures; they were originally published in italic font, due to a publisher error.